Avena sativa L. NGB 6985 ... - GLIS Of The ITPGRFA (Nordgen, 2024)
Plant Genetic Resource. Taxonomy: Avena sativa L. Common name(s): Oat Other names: Lapponia Conserved by: Nordgen (NORDGEN), Sweden Local sample unique identifier: NGB 6985 Method of creation: Acquisition Date: 1988-11-01 Historical: No Biological status: Advanced or improved cultivar MLS status: Included ...